Long-term excessive application of K2SO4 fertilizer alters bacterial community and functional pathway of tobacco-planting soil - Lu, Ya; Cong, Ping; Kuang, Shuai; Tang, Lina; Li, Yuyi; Dong, Jianxin; Song, Wenjing (Frontiers in Plant Science, 2022)
Potassium (K) is essential for tobacco growth. However, the excessive application of K in the pursuit of tobacco quality results in a large amount of K+ and SO42- remaining in the soil. The effects of K2SO4 application on soil acidification and microbial community are still unclear. An eight-year field experiment with three kinds of K2SO4 amounts (low amount, K2O 82.57 kg hm-2, LK; moderate amount, K2O 165.07 kg hm-2, MK; high amount, K2O 247.58 kg hm-2, HK) was established to assess the effects of K2SO4 application on the physicochemical and bacterial characteristics of tobacco-planting soil using 16S rRNA gene and metagenomic sequencing approaches. Results showed that HK and MK led to lower pH and higher nitrogen (N), K, sulfur (S) and organic matter (OM) contents of the soil than LK. HK exposure had a strong stress effect on bacterial communities and metabolic pathways compared to LK. Some eutrophic or resistant species (e.g. Proteobacteria phylum, Bacillus genus) were significantly more abundant in HK than LK. Meanwhile, some oligotrophic taxa (e.g. Acidobacteria phylum) exhibited adverse responses to HK. While the bacterial community compositions of MK and LK were similar. Metagenomic analysis suggested that the improvement of pathways related to carbohydrate metabolism and genetic information processing by HK might be the self-protection mechanism of microorganisms against environmental stress. And pH was the most important factor in shaping bacterial communities and functional composition. In summary, K2SO4 fertilizer should be used cautiously in tobacco fields due to the soil acidification and poor growth of plants by 8-year excessive application of K2SO4.